الضمانات القانونية لحماية حق المستثمر في العقار الاقتصادي - الأعور, بثينة; مباركية, ثورية (University of Eloued جامعة الوادي, 2023)
Résumé .في ظل اطار حماية العقار الإقتصادي نص المشرع على عدة ضمانات قانونية تضمن حقوق المستثمر سواء كان وطني أو أجنبي. حيث كرس هذه الحماية من خلال عقد الإمتياز الصناعي الذي يعتبر آلية قانونية لحماية العقار، وكذا التسجيل لدى الوكالة الوطنية الجزائرية لترقية الإستثمار يعد ضمان لحماية المستثمر من خلال إجراء التسجيل الذي يضمن حقوق المستثمر .أما بما يخص الضمانات الاخرى فقد تطرقنا إلي الضمانات القانونية كمبدأ حرية الإستثمار ومبدأ المساواة بين المستثمرين، مبدأ الثبات التشريعي. حيث تعتبر هذه المبادئ ركيزة قانونية تساعد على جذب المستثمر بالإضافة إلى ذلك الضمانات المالية التي تتمثل في حق تحويل رؤوس الأموال للمستثمرين الأجانب حيث لا يمكن أن يقبل مستثمر على إنشاء مشروع إستثماري اذا لم يكن بإمكانه تحويل ولو جزء من الأرباح التي يجنيها. أما بالنسبة للضمانات القضائية فهي تتمثل في حق اللجوء للقضاء في حالة ما كان هناك نزاع بين الأشخاص الطبيعيين أو المعنويين. وكذا اللجوء إلى التحكيم الدولي في حالة إذا تخوف المشرع الأجنبي من إستيفاء حقه عند عرض النزاع على القضاء الوطني. Abstract .As part of the protection of economic Real estate, the legislator has provided for several legal guarantees that guarantee the rights of the investor, whether national or foreign. This protection is enshrined through the industrial concession contract, which is a legal mechanism for the protection of the property, as well as registration with the Algerian national investment promotion agency is a guarantee of investor protection through the registration procedure which guarantees the rights of the investor. As for the other guarantees, we have touched on legal guarantees such as the principle of freedom of investment and the principle of equality between investors, the principle of legislative stability. These principles are considered as a legal pillar that contributes to attracting the investor, in addition to the financial guarantees represented by the right to transfer capital to foreign investors, when an investor cannot agree to set up an investment project if he cannot transfer even a part of the profits he makes. As for judicial guarantees, they consist in the right to resort to justice in the event of a dispute between natural or legal persons. As well as recourse to international arbitration in the event that a foreign legislator fears that his right will not be respected when the dispute is submitted to national justice.
مذكرة ماستر
Keywords: الضمانات القانونية – العقار الاقتصادي - الاستثمار; Legal guarantees-economic Real Estate-Investment